Open innovation with universities in family firms: can it help to overcome an economic crisis? - Soler-Porta, Mariano (IFERA 2021, 2021)
In this paper, after conducting a review of the literature on innovation in family firms, it has been detected that there is a research gap in relation to the development and results of Open Innovation (OI). In particular, there is a paucity of publications explaining the intersection between OI involving Higher Education Institutions (HEIs) and the overcoming economic crisis. This work proposes a framework to analyse the differences between Family and no family business in the overcoming of an economic crisis, in the context of OI involving HEIs.
Keywords: Open Innovation; Illinois, U.S.A.; Higher Education Institutions (HEIs)